Boosting carry with equilibrium exchange rate estimates - Micha± Rubaszek; Joscha Beckmann; Michele Ca'Zorzi; Marek Kwas (European Central Bank (ECB), 2022)
We build currency portfolios based on the paradigm that exchange rates slowly converge to their equilibrium to highlight three results. First, this property can be exploited to build profitable portfolios. Second, the slow pace of convergence at short-horizons is consistent with the evidence of profitable carry trade strategies, i.e. the common practice of borrowing in low-yield currencies and investing in high-yield currencies. Third, the predictive power of equilibrium exchange rates may boost the performance of carry trade strategies.
Keywords: F31; G12; G15; 330; Equilibrium Exchange Rate; Carry Trade; Trading strategies